Validasi Pengembangan Modul Ajar Evolusi Berbasis Problem Based Learning (PBL) - Vina Safitri; Syamsurizal Syamsurizal; Helendra Helendra; Ria Anggriyani (ISLAMIKA, 2023)
This study aims to produce valid problem-based learning (PBL) evolutionary teaching modules for phase F SMA/MA. The teaching module is a teaching tool for the Independent Curriculum which is designed systematically as a teacher's guide in carrying out the learning process. The research and development method used is the Four-D model development research. This research model consists of four stages, namely define, design, develop and disseminate. The disseminate stage was not carried out due to time constraints. The subjects of this study consisted of two lecturers from the Department of Biology FMIPA UNP and six Biology teachers. This research resulted in a valid problem-based learning (PBL) evolution teaching module with a validity value of 88.26%.